The Relationship between Body Dissatisfaction and Self Esteem among University X Students in Bandung City - Damara Sastri, Prinska; Farisan Akbar, Rifqi; Prameswari Putri Djaelani, Bella; Saidah Wahdah, Neng (International Journal of Psychology and Health Science, 2024)
Having a good image and attraction to students is a big thing. With a bad body image, concerns arise within the individual. This research examines the relationship between body dissatisfaction (body dissatisfaction) and self-esteem (self-esteem) in Psychology students at the University of Indonesia. The method used in this research is a quantitative method with nonprobability sampling and purposive sampling techniques. The total research sample was 34 participants using the Multidimensional Body Self Relations Questionnaire-Appearance Scales (MBSRQ-AS) and Rosenberg Self-Esteem Scale. Based on the results of the analysis, it shows that 50% of respondents have a high level of body dissatisfaction and 58.8% have low self-esteem. And the research results show a significant relationship between body dissatisfaction and self-esteem with a calculated t value of 2.498 which is greater than the t table of 2.0324 at a significant level of 0.018 (p < 0.05), which means that body dissatisfaction has a significant effect on self-esteem. self. This research emphasizes the importance of attention to body image issues that help individuals feel more comfortable and satisfied with their own bodies, and suggests that students learn to love themselves and be more aware of their abilities to increase their self-confidence.